Chloride ion transport and overexpression of TMEM16A in a guinea‐pig asthma model. Issue 6 (20th February 2017) - Kondo, M.; Tsuji, M.; Hara, K.; Arimura, K.; Yagi, O.; Tagaya, E.; Takeyama, K.; Tamaoki, J.
Summary: Background: TMEM16A, a Ca‐activated Cl channel, regulates various physiological functions such as mucin secretion. However, the role of TMEM16A in hyper‐secretion in asthma is not fully understood. Objective: The aim of this study is to evaluate Cl ion transport via TMEM16A and determine the localization of TMEM16A in a guinea‐pig asthma model. Methods: Guinea‐pigs were sensitized with ovalbumin (OVA) i.p. on Days 1 and 8. On Day 22, we assessed OVA challenge‐induced Cl ion transport in the sensitized tracheas ex vivo in an Ussing chamber, compared with the non‐sensitized tracheas. We then examined the effect of T16Ainh‐A01, a TMEM16A inhibitor, on the increase in Cl ion transport. The tracheal epithelium was immunostained with an anti‐TMEM16A antibody. Epithelial cells from guinea‐pig tracheas were cultured at the air–liquid interface in the presence of IL‐13 for in vitro study. We studied the effect of TMEM16A inhibitors on Ca‐dependent agonist, uridine triphosphate (UTP)‐induced increases in Cl ion transport in the cultured cells. The cells were immunostained with an anti‐TMEM16A antibody, an anti‐MUC5AC antibody and an anti‐α‐tubulin antibody. Results: OVA challenge induced an increase in short circuit current within 1 min in the OVA‐sensitized tracheas but not in the non‐sensitized tracheas, which was inhibited by pretreatment of T16Ainh‐A01. Sensitized tracheas showed goblet cell metaplasia with more positive TMEM16A immunostaining, particularly in the apical portion compared with the non‐sensitized tracheas. The in vitro UTP‐induced increase in Cl ion transport was strongly inhibited by pretreatment with T16Ainh‐A01, benzbromarone, and niflumic acid. TMEM16A was positively immunostained at the apical portion and in the MUC5AC‐positive area in IL‐13‐induced goblet cell metaplasia. Conclusions: Antigen challenge and Ca‐dependent agonist treatment increased Cl ion transport via the overexpression of TMEM16A in goblet cell metaplasia in a guinea‐pig asthma model. TMEM16A inhibitors may be useful for the treatment of hyper‐secretion in asthma.